Directions, benefits, and digitalisation effectiveness determining - O. A. Zemlyanskiy (Вестник университета, 2022)
The digital technologies’ development requires the determination of directions and advantages of their implementation and using, designing the ways and implementation structure. The article proposes the directions and marks advantages of introduction, use, and development of digital technologies, and identifying and analysis of market entities and the structure of their interaction. It will allow differentiating such interaction by groups of entities and detail the possibilities, and the ways of digital technologies using in all areas of implementation, and will contribute to achieving the benefits from digitalisation of business activities’ various types. Matrixes for the digital technologies using and matrixes for using the digital technologies’ effectiveness for authorities and business structures have been proposed. The compilation and analysis of these matrixes will make it possible to identify the most attractive areas for the introduction of digital technologies and ways for the development and interaction of business structures and all market entities.